'Pulling the Bandage Off': Using Margaret Warner's 'Fragile Process' in the Psychodynamic Approach. (10th May 2022) - Hauser, Holt J.S.
Abstract : This article explores the nature of how therapists work with clients who find it difficult or impossible to be emotionally or relationally present in therapy. In trying to explore how to be with clients in this challenging state, the author draws from person‐centred theorist Margaret Warner's concept of 'fragile process', and how it describes the presentation of these clients and the therapists' role with them. The author then argues for the utility of this person‐centred concept and its applicability in the psychodynamic approach, and wonders how it might be theoretically conceived in psychodynamic terms for use by psychodynamic practitioners. The author draws parallel between Warner's idea of fragile process with fundamental theoretical understandings of the infant–mother relationship from the theories of Donald Winnicott. After exploring a theoretical understanding of this concept, the author explores his own clinical experience of a client exhibiting fragile process, inspecting a single session. The author offers his account on the case study's contents, the transference material, and the practitioner's reflective process to demonstrate how fragile process as a concept might be applied in client work.